UJI AKTIVITAS ANTI INFLAMASI EKSTRAK ETANOL DAUN BUNI (Antidesma bunius L. Spreng) TERHADAP TIKUS PUTIH (Rattus norvegicus) - Mukhriani Mukhriani; Nurshalati Tahar; Muhammad Rusdi; Khaerani Khaerani; Mutia Fitri Almaidah (Universitas Islam Negeri Alauddin Makassar, 2020)
One of medicinal plant empirically used for traditional is buni leaves (Antidesma bunius L. Spreng) This plant is potential to be developed as medicine for anti-inflammatory. A research on anti-inflammatory activity test of ethanol extract buni leaves (Antidesma bunius L. Spreng) to mice with Rat hind paw edema method. The purpose of study was to investigate the anti-inflammatory activity of the ethanol extract buni leaves (Antidesma bunius L. Spreng) to mice induced with carrageen. The research has done by giving orally suspension of ethanol extract buni leaves (Antidesma bunius L. Spreng) in the dose 5 mg/kg BB, 50 mg/kg BB, and 500 mg/kg BB, Sodium CMC 1% w/v as control negatove and Sodium Diclofenac as control positive. Measurements were made every hour for six hours used plethysmometer. The result after statistically analyzed using Complete Randomized Design showed that dose of 5 mg/kg BB, 50 mg/kg BB and 500 mg/kg BB have anti- inflammatory activity. The result of Duncan’s Real Distance Different test (BNJD) dose 50 mg/kg BB showed that anti-inflammatory activity did not significantly different with Sodium Diclofenac ((α = 0,05).